The effect of bone morphogenetic proteins BMP in comparison with A Xenograft in the management of bone defects - Lutfallah Alhalabi; Mazen Zenati (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Background: The aim of this study is to compare the effect of Bone Morphogenetic Proteins (rhBMP), carried on a gelatin sponge scaffold in comparison with the Xenograft BioOss® in the management of bone defects. Case presentation: The case is a one-year-old rabbit that had 4 identical holes 5*5 mm within the femur bone, BMP2 was placed within the first hole with a gelatin sponge, and the second defect was left empty. A gelatin sponge was placed alone within the third hole, and a BioOss® graft was placed within the last defect. The radiographic evaluation was conducted (1 and 2) months after the surgical work, and the histological assessment was conducted two months after the surgical work. Results: The results of the radiographic evaluation found that healing the BMP2 hole was better than healing in the empty and the gelatin sponge group holes. There was no big difference between the healing in the holes filled with rhBMP2 with gelatin sponge and the healing in the holes filled with BioOss®. Conclusion: The use of a gelatin sponge impregnated with Bone Morphogenetic Proteins improves and accelerates the healing of bone defects and is comparable to the effectiveness of using a BioOss® graft.